Women and development - Rathod, P. B., 1958- (Jaipur, India : ABD Publishers, 2009)
In Indian context.
Includes index.
Includes bibliographical references (p. [344]-351) and index.
Keywords: Women in development -- India; Women -- India -- Social conditions; Women -- India -- Economic conditions; Women -- Government policy -- India